2023
DOI: 10.1128/msystems.00564-22
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Interaction between Phages and Bacteria in an Artisanal Raw Milk Cheese Microbial Community

Abstract: Our work demonstrated a dynamic yet stable microbial ecosystem during cheese production using an endogenous starter culture. This was observed across several distinct producers and was marked by genomic evidence of continued phage-bacterium interactions, such as the presence of bacterial defense mechanisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Recent studies of cheese samples using viral metagenomics (24,25) or exploration of cheese microbial metagenomes (30) have revealed that the cheese environment harbours a diverse bacteriophage community whose targets go beyond lactic acid starter cultures. The isolation of a few representatives of these non-starter phages (27)(28)(29) suggests that phage activity occurs in this ecosystem, raising the question of their overall impact on microbial successions during the ripening process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of cheese samples using viral metagenomics (24,25) or exploration of cheese microbial metagenomes (30) have revealed that the cheese environment harbours a diverse bacteriophage community whose targets go beyond lactic acid starter cultures. The isolation of a few representatives of these non-starter phages (27)(28)(29) suggests that phage activity occurs in this ecosystem, raising the question of their overall impact on microbial successions during the ripening process.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the most studied dairy phages are Lactococcus , Streptococcus , Lactobacillus and Leuconostoc phages, infecting the main starter cultures (22). Viral metagenomics has been recently employed to characterize the bacteriophage communities in dairy samples, including whey (23) and cheeses (24, 25). These investigations have demonstrated that such viral communities are not restricted to LAB phages, but encompass a diverse array of phages that could potentially also infect non-inoculated and ripening bacteria during cheese production.…”
Section: Introductionmentioning
confidence: 99%
“…Backslopping can be considered as a top-down microbiome engineering approach as it allows the selection of communities increasingly adapted to technological pressures (milk, temperature, salt, pH) while assuring desired functions (11) such as acidification. Omics approaches have been used to unravel key features of microbial community dynamics during backslopping, and the consequences for community function (15)(16)(17)(18)(19)(20). Long-term backslopping leads to communities with low species richness and high intraspecies diversity (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Pingo is a natural starter culture composed of fermented whey from the previous day’s batch, containing lactic acid bacteria (LAB)—such as those from the genera Lactobacillus , Lactococcus , Streptococcus , and others [ 8 ]. The most abundant bacterial species in the pingo from Canastra cheese are Lactococcus lactis , Streptococcus thermophilus , Streptococcus infantarius , Streptococcus salivarius , and Corynebacterium variabile [ 9 ]. Additionally, a portion of the cheese that is grated after the ripening process and known as rala could be considered as a substitute for pingo .…”
Section: Introductionmentioning
confidence: 99%